Peradaban Perspektif Al-Qurâan - Mardan, Mardan (Fakultas Adab dan Humaniora UIN Alauddin, 2014)
Muslims regard him as a great civilization. But in Indonrsia, Muslims were not able to demonstrate the existence of the Islamic civilization, because in general, Muslim nations are under the feet of colonization, poor, in ignorance and backwardness. In the perspective of the Quran, the quality of a person is determined by his faith in Allah. Is being determined by the quality of the faith of its science,; while quality is determined by the extent to which science has been practiced. Practice-practice knowledge that is based on the true faith of both physical-material and moral-spiritual that is, in essence,